Desafios da comunicação no processo de crise organizacional:o caso Playcenter - Maradei, Anelisa (2013)
The work is the result of research carried out on the management of Communication in processes of organizational crisis. It seeks to understand how the information flow is currently carried out at these moments, whether through traditional media or online social networks, and, in this way, bring contributions to the performance of organizations from an ethical perspective. In methodological terms, the research is based on the case study of the management of the Playcenter Crisis Communication, which took place in April 2011. Bibliographic review, journalistic analysis, Twitter posts, and semi-structured interviews are used. The results reveal that the image is not a matter of emission, but of reception, a result of diverse perceptions and that these phenomena, today, have been potentialized by the rapid propagation of the facts facilitated by the intenet. However, there is still a strong role of traditional media in these episodes, strong convergence between traditional media and new media, as well as convergence among citizens in the propagation of the facts. (AU)